Incidence Of Thrombocytopenia During Therapy With Bovine Lung And Porcine Gut Mucosal Heparin Preparations - Kwaan, H C; Kampmeier, P A; Gomez, H J (Thrombosis and Haemostasis, 1981)
Thrombocytopenia complicating heparin therapy is always alarming since the bleeding risk is greatly increased. The observations of Bell et al (Ann Int Med. 85:155, 1976) of a 30% incidence of thrombocytopenia in patients receiving bovine lung heparin was not supported by later reports from Powers et al (JAMA 241:2396, 1979) of only 3.4%. However, the latter study involved the use of heparin prepared from porcine gut mucosal. A prospective randomized study of these two respective heparin preparations was carried out at the VA Lakeside Medical Center on 98 patients to whom heparin therapy was given for the treatment of various forms of thromboembolism. All received a heparin dose that prolonged the activated partial thromboplastin time to l1/2-21/2 times the control level for at least 5 days. 86 patients had heparin for 7 or more days. The observation of platelet counts was carried out for 7 days. 10 patients (10.2%) had a fall in their platelet counts to less than 150×l06/dl during therapy with one of the ten having a platelet count of 95×l06/dl on the 4th day of therapy. All but one of the thrombocytopenias were transient, lasting 1-6 days despite continuation of heparin therapy. Of 49 patients who received porcine heparin, 4 (8.2%) had thrombocytopenia while the incidence was 6 out of 49 (12.2%)in those who received bovine heparin. These results suggest that complications of severe thrombocytopenia are uncommon with heparin derived from both sources.